(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The given article is considered as analysis of possibility to create dairy cluster in Issyk-Kul province within the Kyrgyz Republic Presidential Decree #1 of January 11, 2019 «On declaring 2019 the year of regional development and digitalization of the country» and «Biotechnological cluster Ural-Eurasia»